Maintaining Islamic Values In English Language Teaching In Indonesian Pesantrens - Umam, Chothibul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
This paper tries to propose some ways to incorporate Islamic values in Englishteaching in Indonesian pesantrens. Among others things these values include:optimizing the use of instructional materials containing Islamic messages andpreparing teachers with multiple qualifications. By so doing, the santris canmaintain their Islamic identity and are not easily contaminated by Westernvalues and, at the same time, they will have English competence as a means toface their future.